Pattern of human dhole interaction in buffer area of Jigme Khesar Strict Nature Reserve - Dorji, Phub (International Journal of Scientific Research and Management (IJSRM), 2021)
Human-wildlife conflict is a serious problem to conservation efforts worldwide. This is also true for Bhutan, where carnivores depredate livestock of farmers, affecting farmer’s livelihood, however, there is sparse documentation on the extent of human dhole interaction in Bhutan’s some of the important areas of conservation interest. Therefore the aim of this research was to evaluate the extent of human dhole interaction, income lost due to depredation and the perception of the farmers towards dhole conservation. Data were collected from 160 households within two strata of rural and semi-urban area in western Bhutan through semi-structured questionnaire and focused group discussions. Livestock depredation involved seven predators, which caused loss of 5% of the total average annual income of the farmers; which were significantly different between the predators involved. Dhole killed significantly more livestock than other predators and maximum kills were made in rural area than semi urban area. 60% of the incomes lost due to wild predators were caused by dhole with major impact in rural area. Majority of the respondents from rural area exhibited negative attitude towards dhole conservation. They suggested livestock depredation compensation schemes and other livelihood alternatives to minimize the impact of conflict, whereas majority of the respondents from semi-urban suggested electric fencing around their village as measures to reduce human wildlife conflict. Livestock compensation and insurance schemes, integrated conservation development programs, educational outreach programs with other livelihood alternatives such as ecotourism are recommended as intervention strategies to minimize human dhole conflict and create harmonic co-existence.